English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-26 04:22:15 · 17 answers · asked by porcha b 1 in Science & Mathematics Mathematics

17 answers

3(x+3y)+4(2x-4y)
distribute : 3x+9y+8x-16y
combine like terms: 11x-7y
answer: 11x-7y

2006-12-26 04:25:55 · answer #1 · answered by Anonymous · 1 0

Q : 3(x+3y) +4(2x-4y)
A :step 1; multiply
3x+9y+8x-16y
step2; add the coeffecients of the same variables
i.e., 3x+8x+9y-16y
11x -7y
3(x+3y)+4(2x-4y) = 11x-7y is the required answer.

2006-12-26 05:27:57 · answer #2 · answered by Anonymous · 0 0

First: use distribution:

3(x) + 3(3y) + 4(2x) - 4(4y)

3x + 9y + 8x - 16y

Second: combine "like" terms:

3x + 8x + 9y - 16y

11x - 7y

2006-12-26 12:53:00 · answer #3 · answered by ♪♥Annie♥♪ 6 · 0 0

Your first step would be to distribute the 3 and the 4 over their respective set of brackets.

3x + 9y + 8x - 16y

Now, group like terms.

11x - 7y

2006-12-26 04:29:51 · answer #4 · answered by Puggy 7 · 1 0

Distribute the first terms:
3x+9y+8x-16y

Simplify:
11x-7y

2006-12-26 04:27:25 · answer #5 · answered by John C 1 · 1 0

3(x + 3y) + 4(2x - 4y) = 0

3x + 9y + 8x - 16y = 0

11x - 7y = 0

The answer is 11x - 7y = 0

- - - - - - - - -s-

2006-12-26 05:46:58 · answer #6 · answered by SAMUEL D 7 · 0 1

=3x +9y + 8x -16 y = 11x-7y

2006-12-26 04:26:21 · answer #7 · answered by Frederic R 3 · 1 0

a million.. 3x^2 + 4x + 3x^2 - 4y = 6x^2 + 4( x-y) = 2 [ 3x^2 + 2 (x-y) 2.. (5x-2y) - (4x+8y) = 5x -2y - 4x - 8y = x -10y 3. 3x^3(2x^2) = 6x^6 4. 5x^3y^4z/10xy^2z^3 = x^2y^2/ 2z^2 5.(-6a^3b^4)^2= 36a^6b^8 6.(x+9)(x-9)= (x^2-80 one) 7.(3x-7)^2= 9x^2 - 42x + 40 9= (3x-7)(3x-7) 8.(3x+6)(4x-7)=12x^2 -21x +24x -40 two= 12x^2 +3x -40 two =3(4x^2+x -14) 9. 5x^3y + xy^4 +2xy/xy =xy(5x^2 +y^3 +2)/ xy =5x^2 +y^3 +2 10..15ab +6ab^4 +24b/3b =3b(5a + 2ab^3 +8)/3b =5a+2ab^3 +8= a(5+2b^3)+8 whats up there!! it quite is my answer yet you should use the single that extra wholesome you and stay away from something

2016-11-23 17:57:02 · answer #8 · answered by Anonymous · 0 0

= 3x + 9y + 8x - 16 y = 3x + 8x + 9y - 16y = 11x -7y

2006-12-26 04:27:46 · answer #9 · answered by saudipta c 5 · 1 0

3x+9y+8x-16y
11x-7y My final answer♥

2006-12-26 04:26:38 · answer #10 · answered by ♥USMCwife♥ 5 · 1 0

fedest.com, questions and answers